1997
DOI: 10.1038/sj.onc.1201242
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-independent activation of fibroblast growth factor receptor-2 by carboxyl terminal alterations

Abstract: To assess the e ect(s) of the C-terminal domain on FGFR2 function, we engineered a series of mutant FGFR2 cDNAs encoding deletions in the C-terminus of the receptor and compared their growth properties in NIH3T3 ®broblasts. In contrast to FGFR2-WT, receptors with C-terminal truncations induced ligandindependent transformation of NIH3T3 cells and transfectants expressing these mutant receptors eciently formed colonies in semisolid medium. Introduction of point mutations (Y to F) into the C-terminus of FGFR2 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 28 publications
1
23
0
2
Order By: Relevance
“…Our results, demonstrating that the Ksam-IIC3 receptor, which lacks 54 aa of the C-terminal domain, does not inhibit growth, demonstrate the importance of this domain for the growth inhibitory activity of FGFR2b and confirm the results of previous studies showing that the two receptors may display different biological roles in cell growth, cell transformation and differentiation (Ishii et al, 1995;Lorenzi et al, 1997). These studies showed that the short carboxy-terminal form of the receptor had stronger transformation activity.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Our results, demonstrating that the Ksam-IIC3 receptor, which lacks 54 aa of the C-terminal domain, does not inhibit growth, demonstrate the importance of this domain for the growth inhibitory activity of FGFR2b and confirm the results of previous studies showing that the two receptors may display different biological roles in cell growth, cell transformation and differentiation (Ishii et al, 1995;Lorenzi et al, 1997). These studies showed that the short carboxy-terminal form of the receptor had stronger transformation activity.…”
Section: Discussionsupporting
confidence: 80%
“…Two isoforms of the receptor, FGFR2b and Ksam-IIC3, which differ in the carboxy-terminal domain, have been described and have very different growth-activating properties (Ishii et al, 1995;Lorenzi et al, 1997;Sakaguchi et al, 1999). We therefore investigated the growth inhibitory properties of Ksam-IIC3, the isoform with the short carboxy-terminal domain (Figure 4a).…”
Section: The Distal Carboxy-terminal Portion Of Fgfr2b Is Involved Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we and others have previously found that although activating Ras or Raf transforms fibroblasts, only Ras but not Raf transforms epithelial cells, suggesting that distinct mechanisms exist for Ras transformation in epithelial cells and fibroblasts (12,13). The majority of studies have evaluated the transforming potential of FGFR2 IIIb in NIH 3T3 mouse fibroblasts (6,14,15). NIH 3T3 cells express KGF and a KGF monoclonal antibody blocked FGFR2 IIIb C1 transformation of NIH 3T3 cells.…”
Section: Introductionmentioning
confidence: 99%
“…The FGFR2-WT was previously constructed as a chimera consisting of the ectodomain of FGFR2 and the intracellular domain of the wild-type KGFR and represents a wild-type FGFR2 containing two Ig loops and an acidic domain (Lorenzi et al, 1996). KGFR and FGFR2-ET have been described elsewhere (Miki et al, 1991a;Lorenzi et al, 1997). Focus formation assays were performed as described (Miki and Aaronson, 1995).…”
Section: Expression Cloning and Functional Analysis Of Kgfr-pamentioning
confidence: 99%